Core belief challenge moderated the relationship between posttraumatic growth and adolescent academic burnout in Wenchuan area during the COVID-19 pandemic - Zeng, Zhengyu; Wang, Xiaogang; Chen, Qiuyan; Gou, Yushi; Yuan, Xiaojiao (Frontiers in Psychology, 2022)
This study investigates the characteristics of posttraumatic growth (PTG) and academic burnout among adolescents in an ethnic minority area in China during the COVID-19 pandemic, and examines the moderating role of core belief challenge on the association between PTG and academic burnout. This study surveyed 941 secondary school students in Wenchuan using the posttraumatic growth inventory, adolescent academic burnout inventory, core beliefs inventory, and a self-designed demographic questionnaire. The results showed that: (1) Five months after the COVID-19 outbreak in China, the level of PTG among adolescents in the Wenchuan area was high and its prevalence was 32.3%. Among them, the dimension of perceived changes in self was the highest, and the PTG level of junior high school students was higher than that of high school students. The academic burnout level of adolescents, particularly emotional exhaustion, was also high. The academic burnout level of the high school students was higher than that of junior high school students. (2) There was a significant negative correlation between PTG and academic burnout among adolescents. (3) Core belief challenge moderated the relationship between PTG and academic burnout. PTG had a significant negative predictive effect on adolescents’ academic burnout only when the core belief challenge was above a moderate level. These results showed the uniqueness of PTG and psychological behavioral problems of adolescents in ethnic minority areas during the COVID-19 pandemic. They also emphasized the key role of core belief challenge in the process of PTG in reducing adolescents’ academic burnout. Based on these results, recommendations are provided to alleviate academic burnout among adolescents in Wenchuan against the background of the COVID-19 pandemic. While providing full play to ethnic minority cultural characteristics to promote posttraumatic growth, guiding adolescents’ value reflection and cognitive reconstruction should be focused on.